The Relationship betweem school feeding and family agriculture in the municipality of Guaraniaçu - PR - Cassol, Bruna; Mary Guimarães Nogueira, Francis (Guará Journal, 2022)
The objective of this study was to verify how the connection between school feeding and family farming (FA) occurred in the municipality of Guaraniaçu, after the enactment of Law 11.947/2009. This is a qualitative research, involving a case study, carried out in two municipal schools, one located in the city and the other located in the rural area. The research invol-ved bibliographical consultations and field research, with the application of questionnaires and interviews with people rela-ted to family agriculture and school feeding in the municipality. The data were analyzed based on the analysis of content in the thematic modality of Minayo (2007), resulting in three final ca-tegories. It is considered the relevance of cooperativism for fa-mily farming in the municipality studied, which guaranteed in-come and work for family farmers. The insertion of FA products was important for improving the quality of the children’s food, because the characteristics of these products are natural, fresh, minimally processed and respect the municipality’s regionali-ty. Finally, it is considered that the school is a space conducive to the formation of healthy eating habits in children, since they spend a good part of their day at school